Pengembangan Usaha Ternak Sapi Potong Rakyat Berbasis Sumber Daya - Bagus Kesan Besari Ramadhan; Amam; Sukron Romadhona; Supardi Rusdiana (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Abstract Smallholder farmers maintain beef cattle based on previous experience and information from fellow farmers. Success in livestock business is influenced by several aspects, both internally and externally. The purpose of the study was to determine the effect of resource support on the development of smallholder beef cattle farming business. The research was conducted in Jetis Village, Curahdami Sub-District, Bondowoso District. The research variables consist of livestock farming business development (Y), economical resources (X1), social resources (X2), and environmental resources (X3). Methods of data collection is done by observation and survey. Data analysis was performed using the Partial Least Square (PLS) method using the SmartPLS 2.0 application. The results showed that livestock farming business development consisted of 4 (four) indicators, economical resources consisted of 5 (five) indicators, social resources consisted of 5 (five) indicators, and environmental resources consisted of 4 (four) indicators. The conclusion of the study shows that economical resources, social resources, and environmental resources have a positive and significant 38.9% effect on the development of smallholder beef cattle farming business. Keywords: Resources, Beef Cattle, Smallhoulder Farming. Livestock Farming Business Development.